2019
DOI: 10.1002/pssb.201900411
|View full text |Cite
|
Sign up to set email alerts
|

Large Graphene Oxide Flakes: From Isotopic to Nematic Liquid Crystal Phase Transition

Abstract: Herein, graphene oxide (GO) with large flakes of average size 38 μm is studied, following the isotropic–nematic phase transition over time and determining the critical concentration, i.e., the minimum value for the formation of the pure liquid crystal (LC) phase. The GO flakes in aqueous suspensions can form LC phases, which are attractive for various applications because of their exceptional properties. Stability over time is very important for their applications, especially, if the GO suspension is in the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Figure 1A shows that the LC phase is well established even at a low concentration. The bright area represents the nematic phase of the LC, and a suspension with isotropic properties appears as the black area 36 . Here, we added poly(amic acid) salt (PAAS) to the GO solution to disperse it.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1A shows that the LC phase is well established even at a low concentration. The bright area represents the nematic phase of the LC, and a suspension with isotropic properties appears as the black area 36 . Here, we added poly(amic acid) salt (PAAS) to the GO solution to disperse it.…”
Section: Resultsmentioning
confidence: 99%
“…The bright area represents the nematic phase of the LC, and a suspension with isotropic properties appears as the black area. 36 Here, we added poly(amic acid) salt (PAAS) to the GO solution to disperse it. PAAS has an ionized structure, which gives it higher solubility in various solvents than conventional poly(amic acid).…”
Section: Synthetic Mechanism Of Go/paas Lc Filmmentioning
confidence: 99%
“…Very much like exfoliated GO in aqueous suspension [67,68], exfoliated clay nanolayers in aqueous suspension form entropically driven nematic phases [13,33,34,[69][70][71][72][73]] merely due to their individual platelet shape and thus loss of rotational degrees of freedom. It has been found that also clay particle stacks form nematic phases [14,[74][75][76][77][78] independently of delamination and exfoliation, since also the full particles are platelet shaped, although much thicker than the individual nanolayers.…”
Section: Fig 2 Adopted From Supplementary Informationmentioning
confidence: 99%
“…Since GO flakes are strongly negatively charged, their effective hydrodynamic dimensions – including the hydration shell – should be significantly larger in the aqueous suspension than in the dried state. 19,20 In addition, it was found that GO sheets are not completely rigid, rather they can be considered super-flexible like a 2D polymer and can form folded and wrinkled structures, in particular when dried. 21–24…”
Section: Introductionmentioning
confidence: 99%
“…Since GO flakes are strongly negatively charged, their effective hydrodynamic dimensions -including the hydration shell -should be significantly larger in the aqueous suspension than in the dried state. 19,20 In addition, it was found that GO sheets are not completely rigid, rather they can be considered super-flexible like a 2D polymer and can form folded and wrinkled structures, in particular when dried. [21][22][23][24] A widely applicable tool to investigate the size of colloidal particles in fluid dispersions is dynamic light scattering (DLS), which at first provides information about the diffusion coefficients of the particles.…”
Section: Introductionmentioning
confidence: 99%